ANALISIS GEOSPASIAL HASIL KESEPAKATAN SEGMEN BATAS WILAYAH SEBAGAI UPAYA MEMINIMALISASI POTENSI KONFLIK ANTARA KOTA KEDIRI DENGAN KABUPATEN KEDIRI PROVINSI JAWA TIMUR - Dionisius Putra Perdana Wijaya; Gia Gustaman; Maretta Aviani Susanto; Asri Ria Affriani; Regina Vera Santiara Yahya Putri (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2023)
Territory boundaries are important things that become one of the factors supporting development in the development of a region. Over time, the Government issued Permendagri Regulation No. 45 of 2016 which contains Guidelines for Confirming Regional Boundaries. The research location is on the boundary segment between Kediri Regency and Kediri City. The research objective is to analyze the spatial/geometric quality of boundary segment delineation in Kediri City and the government's efforts to minimize potential conflicts between Kediri City and the Kediri Regency. The method used in this research is geospatial analysis. The research results show that there are differences territory boundaries between the 2022 Boundary Agreement Result Map and the 2019 Regional Administration Map. The difference in delineation forms an agreed area with a total of 67.2 Ha. With the agreement, it can be minimalized conflicts between the two regions involving economic, social, and political etc aspects in the future